REMOVAL OF BARIUM IONS FROM AQUEOUS SOLUTIONS BY BARIUM TITANATE USING RADIOTRACER TECHNIQUE: - S.P.MISHRA; N.SRINIVASU (International Journal of Pharma and Bio Sciences, 2014)
The adsorption of barium ions on barium titanate in an aqueous solution was studied by means of batch technique as a function of Ba(II) concentration, temperature and solution pH using Ba-140 as radiotracer. The results show that adsorption is essentially complete in ca 180min and the steady state values of adsorption at various concentrations agree well with the classical Freundlich isotherm and follow first order kinetics. The pH and temperature of the solution markedly affect the extent of adsorption. Exposure of the activated barium titanate adsorbent to neutrons and γ irradiation from a (Ra-Be) neutrons source having an integral flux of 3.85x106 neutrons/cm2 / sec and associated with a nominal γ does of Ca 172 rads/h, affects its adsorption capacity markedly.